Prospection About Traps to Aedes Aegypti Mosquitoes and Related Technologies - Gois, Antonio Wanderson Vieira (2021)
Aedes aegypti has caused various harms to humanity for centuries, essentially because it’s a vector for many diseases. Due to globalization, the increase in the human population and socio-environmental transformations on the planet, the damages caused by it have worsened considerably. The prospective analysis maps the scenario of innovations and guides strategies of technological development. Therefore, this descriptive study is based on exploratory patent research based on the Derwent Innovation Index database, with quali-quantitative approaches on traps and related technologies for control the Aedes aegypti published between 2000 and 2020. The technologies analyzed point mainly to strategies to eliminate these insects, whereas, to monitor them, it’s necessary to invest more in development of egg traps, and more potent and less environmentally harmful attractants. In short, 57 patent families were identified on the studied technologies, wich have stable and slightly decreasing tendency in applications, with Brazil being the mainly applicant and USA the main focus of applications.